Efektivitas dan Akurasi Metode Manual dan Bim dalam Perhitungan Volume Pile Cap dan Pembesian Bangunan Gedung - Gazalba Imaduddin Sholeh (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
In the modern construction industry, accuracy and efficiency in volume calculations are crucial aspects of project success. This study compares two methods for calculating the volume of pile caps and reinforcement: the manual method and the Building Information Modeling (BIM)-based method. The manual method has long been used but has limitations in terms of time efficiency and a higher risk of errors. In contrast, the BIM method offers more accurate and efficient calculations through software-based digital modeling. This study employs a descriptive-comparative quantitative approach by analyzing volume calculation data using both methods. The results indicate that the BIM method has a higher level of accuracy, with a concrete volume of 1,822.87 m³ and reinforcement of 148,862.80 kg, compared to the manual method, which produced a concrete volume of 1,842.17 m³ and reinforcement of 150,279.05 kg. The comparison of pile cap volume calculations shows that the BIM method achieves 98.95% effectiveness in concrete volume calculations and 99.06% effectiveness in reinforcement calculations compared to the manual method. Additionally, the BIM method has proven to be more efficient in reducing calculation time and minimizing input errors. Thus, BIM is more recommended for large-scale projects that require high accuracy and efficiency in construction volume calculations. However, the manual method remains relevant as a validation tool and for small projects with technological limitations. This study highlights the importance of adopting digital technology in the construction industry to enhance productivity and project planning effectiveness.